Guidelines for the programmatic management of drug-resistant tuberculosis : [emergency update 2008] - 4 0 16; Jaramillo, Ernesto; Department for International Development.;Agency for International Development. 5 Stop TB Initiative (World Health Organization);Great Britain.;United States (Geneva : World Health Organization, Stop TB Department, 2008)
The emergence of extensively drug-resistant strains of tuberculosis, especially in countries with a high prevalence of human immunodeficiency virus, is a serious threat to global public health and jeopardizes efforts to effectively control the disease. This publication offers updated recommendations for the diagnosis and management of drug-resistant tuberculosis in a variety of geographical, economic and social settings, and the recording of data that enables the monitoring and evaluation of programs.--Publisher's description.
Background information on DR-TB -- Framework for effective control of DR-TB -- Political commitment and coordination -- Definitions : case registration, bacteriology and treatment outcomes -- Case-finding strategies -- Laboratory aspects -- Treatment strategies for MDR-TB and XDR-TB -- Mono-resistant and poly-resistant strains -- Treatment of DR-TB in special conditions and situations -- DR-TB and HIV infection -- Initial evaluation, monitoring of treatment and management of adverse effects -- Treatment delivery and community-based DR-TB support -- Management of patients after MDR-TB treatment failure -- Management of contacts of MDR-TB patients -- Drug resistance and infection control -- Human resources : training and staffing -- Management of second-line antituberulosis drugs -- Category IV recording and reporting system -- Managing DR-TB through patient-centred care.
WHO/HTM/TB/2008.402.
Includes bibliographical references and index.
Also available online.
Funded by the UK Department for International Development and the United States Agency for International Development.
Keywords: 2 -- 0; 6; Chemotherapy.;Prevention.;Chemotherapy.;Treatment.;drug therapy.;prevention & control.;administration & dosage.;drug therapy. -- Multidrug-resistant tuberculosis;Multidrug-resistant tuberculosis;Antitubercular agents.;HIV infections;Comorbidity;Highly active antiretroviral therapy.;Tuberculosis, Multidrug-Restant;Tuberculosis, Multidrug-Restant;Antitubercular Agents;HIV Infections;Antiretroviral Therapy, Highly Active. -- 20; 20; 2